Focusing properties of spirally polarized sinh Gaussian beam. (April 2019) - Senthilkumar, M.; Rajesh, K.B.; Udhayakumar, M.; Jaroszewicz, Z.; Mahadevan, G.
Highlights: The tight focusing properties of spirally polarized sinh-Gaussian beam is studied. Focusing properties are investigated theoretically by vector diffraction theory. Optical intensity in focal region can be altered considerably by the spiral parameter. Focal patterns including flattop profile, focal hole, axially separated focal spots are generated. Abstract: The tight focusing properties of spirally polarized sinh-Gaussian beam is investigated numerically by vector diffraction theory. Results show that the optical intensity in focal region of spirally polarized sinh Gaussian beam can be altered considerably by the beam order, relative waist width and the spiral parameter that indicates the polarization spiral degree of the spirally polarized sinh Gaussian beam. Many novel focal patterns including flattop profile, focal hole axially separated focal spots and focal spot with long focal depth are evolved considerably for the suitable beam parameters. We expect such a tunable focal patterns are useful for optical manipulation of micro particles.